HUBUNGAN KONFORMITAS SISWA DENGAN PENGAMBILAN KEPUTUSAN KARIR - Septi Vatmawati (Empati-Jurnal Bimbingan dan Konseling, 2019)
Abstract. Research on Relationship between Student Conformity and Career Decision Making was motivated by the discovery of students who experienced confusion, doubts in determining career choices. The tendency to take career decisions because of joining friends, encouraging parents and teachers who are too hard on one career choice and causing students to make career decisions. This is not in accordance with the potential, talents and interests possessed.This type of research is quantitative research. Ex post fact research method with a correlational approach. The hypothesis in this research are there relationship between student conformity and career decision making. The population used in this study were students of SMK Teuku Umar Semarang class XI 2017/2018 period. Software engineering class was used as a try out class. As for the accounting class and institutional finance as research samples. Sampling used is cluster random sampling technique. This research data is obtained through the scale of student conformity and the scale of career decision making.The results of the correlation analysis between the conformity of students with career decision making is the relationship of conformity of students with career decision making (rxy) of 0.465 strong enough categories. Contribution of conformity of students with career decision making is 21.62% and the remaining 78.38% is determined by other variables. Whereas there was found no significant relationship between students' conformity with career decision making. Because α = 0, 05 and n = 17. Test two parties; dk = n-2 = 17-2 = 15 so ttable 2, 131, it turns out that t count ≤ t table or 2.031 ≤ 2.131 then Ho is accepted which means that there is no significant relationship between the conformity of students and career decision making.Based on the results of this study the suggestions that can be conveyed are finding and helping students to make career decisions effectively and efficiently and maximize the role of BK teachers and related parties in realizing it. Keywords: Career Decision Making, Student Conformity